New Criteria for Response to Treatment in Immunoglobulin Light Chain Amyloidosis Based on Free Light Chain Measurement and Cardiac Biomarkers: Impact on Survival Outcomes - Palladini, Giovanni; Dispenzieri, Angela; Gertz, Morie A.; Kumar, Shaji; Wechalekar, Ashutosh; Hawkins, Philip N.; Schönland, Stefan; Hegenbart, Ute; Comenzo, Raymond; Kastritis, Efstathios; Dimopoulos, Meletios A.; Jaccard, Arnaud; et al. (Journal of clinical oncology, 2012)
To identify the criteria for hematologic and cardiac response to treatment in immunoglobulin light chain (AL) amyloidosis based on survival analysis of a large patient population. We gathered for analysis 816 patients with AL amyloidosis from seven referral centers in the European Union and the United States. A different cohort of 374 patients prospectively evaluated at the Pavia Amyloidosis Research and Treatment Center was used for validation. Data was available for all patients before and 3 and/or 6 months after initiation of first-line therapy. The prognostic relevance of different criteria for hematologic and cardiac response was assessed. There was a strong correlation between the extent of reduction of amyloidogenic free light chains (FLCs) and improvement in survival. This allowed the identification of four levels of response: amyloid complete response (normal FLC ratio and negative serum and urine immunofixation), very good partial response (difference between involved and uninvolved FLCs [dFLC] < 40 mg/L), partial response (dFLC decrease > 50%), and no response. Cardiac involvement is the major determinant of survival, and changes in cardiac function after therapy can be reliably assessed using the cardiac biomarker N-terminal natriuretic peptide type B (NT-proBNP). Changes in FLC and NT-proBNP predicted survival as early as 3 months after treatment initiation. This study identifies and validates new criteria for response to first-line treatment in AL amyloidosis, based on their association with survival in large patient populations, and offers surrogate end points for clinical trials.